Molecular characterisation of Mycobacterium avium subsp. paratuberculosis in Australia - Rachel Hodgeman; Rachel Mann; Keith Savin; Noel Djitro; Simone Rochfort; Brendan Rodoni (BMC Microbiology, 2021)
Abstract Background Mycobacterium avium subsp. paratuberculosis (Map) causes Johne’s disease (JD), a chronic enteritis widespread in ruminants, resulting in substantial economic losses, especially to the dairy industry. Understanding the genetic diversity of Map in Australia will assist epidemiological studies for tracking disease transmission and identify subtype characteristics for use in development of improved diagnostic typing methods. Here we investigated the phylogenetic relationships of 351 Map isolates and compared different subtyping methods to assess their suitability for use in diagnostics and accuracy. Results SNP-based phylogenetic analysis of 228 Australian isolates and 123 publicly available international isolates grouped Type S and Type C strains into two distinct lineages. Type C strains were highly monomorphic with only 20 SNP differences separating them. Type S strains, when aligned separately to the Telford strain, fell into two distinct clades: The first clade contained seven international isolates while the second clade contained one international isolate from Scotland and all 59 Australian isolates. The Australian Type B strain clustered with US bison strains. IS1311 PCR and Restriction Enzyme Analysis (REA) intermittently generated incorrect results when compared to Long Sequence Polymorphism (LSP) analysis, whole genome SNP-based phylogenetic analysis, IS1311 sequence alignment and average nucleotide identity (ANI). These alternative methods generated consistent Map typing results. A published SNP based assay for genotyping Map was found to be unsuitable for differentiating between Australian and international strain types of Map. Conclusion This is the first phylogenetic analysis of Australian Map isolates. The Type C lineage was highly monomorphic, and the Type S lineage clustered all Australian isolates into one clade with a single Scottish sheep strain. The Australian isolate classified as Type B by IS1311 PCR and REA is likely to be descended from bison and most closely related to US bison strains. Limitations of the current typing methods were identified in this study.